Cognitive Behavioral Therapy Using the Redha Concept to Handle the Problem of Depression Among Students : A Pilot Study - Sulaiman, Noor Azimah Binti (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Mental health, especially depression, is a serious global issue. This problem of moodiness affects individuals. This research aims to analyze Cognitive Behavioral Therapy (CBT) which is integrated with the Redha Concept in dealing with the problem of depression among students. This study also adapts an approach that is in line with the cultural and spiritual values of the local community, with the hope of providing more relevant solutions to students' mental health problems. This experimental quantitative study involved 291 Sixth Form students who completed the 21-item Depression, Anxiety and Stress Scale (DASS21) to measure their level of depression. Of this number, 12 students were randomly selected based on their depression stage to take part in the intervention session and complete the Patient Health Questionnaire (PHQ9) at pre- and post-intervention levels. Data analysis was carried out using the Friedman test and the Wilcoxon Signed Rank Test to assess changes in the stages of depression. The results of the study showed a significant reduction in levels of moodiness after therapy sessions, with median scores decreasing from 12.00 to 8.00 (p < 0.001). In conclusion, CBT integrated with the Redha Concept has the potential to be an effective approach in reducing student depression, with implications that show the importance of applying this approach on a wider scale to support students' mental well-being, especially in the cultural and spiritual context of Brunei society.